A decision support model based on q-rung orthopair fuzzy number for glove design application - Efe, Ömer Faruk; Efe, Burak (Springer, 2022)
Quality function deployment (QFD) method allows reviewing of customer requirements (CRs) and design requirements (DRs) simultaneously in order to handle the correlations and relationships of CRs and DRs in calculations. It has been often combined with fuzzy numbers because it provides to gather the judgments of experts in vagueness environment more correctly and easily. This paper suggests employing q-rung orthopair fuzzy number (q-ROFN) for improving the fuzzy QFD approach. The proposed q-ROFN based QFD method uses q-ROFN to adjust the weights of CRs based the relationships between CRs and DRs with the help of the correlations and relationships of CRs and DRs. q-ROFN presents more information than numbers such as intuitionistic fuzzy number and Pythagorean fuzzy number about the correlations and relationships of CRs and DRs. VIKOR (VIsekriterijumska optimizacija i KOm-promisno Resenje) approach based on q-ROFN is also used to rank DRs. The new proposed integrated method has been applied for evaluating the anthropometry based glove design. The results show that the most important DR for anthropometry based glove design is ease of hand motion perception.
Keywords: Quality function deployment; Anthropometry based glove design; VIKOR; q-Rung orthopair fuzzy number